Le alternative prese sul serio. Filosofia sociale, metamorfosi e mutualismo produttivo - Leonard Mazzone (Cambio)
The article claims for social philosophy a public function similar to that claimed in the sociological field by Michael Burawoy. Canetti’s concept of metamorphosis is the best candidate to translate the immanent and heretical normativity of social philosophy: once summarized the core features of this concept and its link with social philosophy, I will focus on a particular case of real utopias: namely, the recovered companies by workers. After presenting the main characteristics of the cooperative recovery of companies in crisis or at risk of delocalization, the contribution will resume the different processes of genesis of recovered enterprises and, at the same time, the main indicators that allow us to interpret them as garrisons of labour democratization and, in some cases, as real actors in processes of social metamorphosis.